1994
DOI: 10.2331/fishsci.60.203
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Feather Meal as a Protein Source in the Diet of Juvenile Japanese Flounder

Abstract: The weight gain of fish fed on the diets containing 12 and 25% of feather meal did not differ from that of fish fed on the control diet containing 80% of white fish meal, however, fish fed on the 37 and 50% feather meal diets gained less weight. The feed conversion efficiency and protein efficiency ratio of fish fed on the 12% feather meal diet were almost the same as in the control group, however, these efficiencies decreased as the proportion of feather meal in the diet increased from 25, 37 to 50%. Suppleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
80
2
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 21 publications
7
80
2
2
Order By: Relevance
“…Unlike this study, however, dietary alternative protein sources affected plasma constituents; for instance, dietary substitution of fishmeal with soybean meal tended to increase serum triglycerides and/or glucose concentration (Kikuchi et al 1994b;Kikuchi 1999b). Plasma total protein and triglyceride level was affected by both dietary protein and lipid levels (Lee and Kim 2005).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Unlike this study, however, dietary alternative protein sources affected plasma constituents; for instance, dietary substitution of fishmeal with soybean meal tended to increase serum triglycerides and/or glucose concentration (Kikuchi et al 1994b;Kikuchi 1999b). Plasma total protein and triglyceride level was affected by both dietary protein and lipid levels (Lee and Kim 2005).…”
Section: Resultsmentioning
confidence: 94%
“…Substitution of fishmeal with animal protein sources, such as meat and bone meal up to 18% , meat meal up to 30% without supplementation of amino acids and 60% with supplementation of amino acids and feather meal up to 40% (Kikuchi et al 1994a) in the diets for olive flounder had been successfully made without retardation of growth. The alternative plant protein sources, such as soybean meal up to 44% (Kikuchi et al 1994b) and corn gluten meal up to 40% (Kikuchi 1999a), and their combination, such as combined blood meal, corn gluten meal and blue mussel meat up to 45% (Kikuchi 1999b) for fishmeal in the diets, were successfully made. Furthermore, Deng et al (2006) showed that performance of olive flounder fed the diets substituting soy protein concentrate for 25-100% fishmeal was poorer than that of fish fed the fishmeal-based diet, but the diets with supplementation of amino acids improved.…”
Section: Introductionmentioning
confidence: 97%
“…As a carnivorous species, it requires a high dietary protein level and has strong dependence on FM, the inclusion level of which is above 50% in its commercial diets (Lim and Lee 2008). Previous studies on the utilization of SBM as a FM alternative for the fish were focused on the effects of dietary SBM inclusion on fish growth and feed utilization (Kikuchi et al 1994;Kikuchi 1999;Saitoh et al 2003;Choi et al 2004;Pham et al 2007). The results showed a relatively low substitute proportion of FM protein with SBM in commercial diets of the species.…”
Section: Introductionmentioning
confidence: 93%
“…The by-products of the processing of terrestrial livestock such as cows, chickens, and pigs could be used as animal protein sources, since they have a relatively high protein content and qualitatively similar amino acid composition to fishmeal, and are inexpensive and stably supplied. Various studies have been conducted on their use as protein sources to replace fishmeal in fish feed [8][9][10][11][12][13]. However, the rise of safety issues due to serious infectious diseases like mad cow disease, swine fever, and avian influenza has gradually restricted the use of livestock by-products lately.…”
Section: Introductionmentioning
confidence: 99%